Los nuevos derechos - Corchete Martín, María José (Teoría y Realidad Constitucional, 2007)
This article attempts to reflect on the hended search to strike a balance between the constancy and the change of the fundamental rights. The Constitution is the starting point of the fundamental rights as a dogmatic category. Therefore it cannot be isolated from the reality if we want it to continue being an alive and effective norm. For this reason the Constitution must introduce this update of rights, which is essential and inevitable taking into account the social, cultural and economic transformations that affect the human being constantly. The research of means and techniques to strike this said balance will lead us to the reality of the fundamental rights at the present time, like a dynamic category.